Climate security policy coherence and awareness analysis: Zambia - Schapendonk, Frans; Scartozzi, Cesare M; Madurga Lopez, Ignacio M.; Meddings, George; Läderach, Peter R.D.; Pacillo, Grazia (2023)
This policy coherence and awareness analysis (PCAA) report assess 54 policies and strategic frameworks produced by the national government of Zambia and the Southern African Development Community (SADC) in order to assess the extent to which sectors relevant to the management of climate-related security risks display awareness of the intersection of climate, peace, and security, as well as the degree to which these sectors display evidence of strategic and operational integration with one another. This report concludes with a set of recommendations aimed at policy and decision-makers in Zambia and Southern Africa to aid the responsiveness of existing policy and strategic frameworks to the intersection of climate, peace, and security.